2021
DOI: 10.1002/jcc.26713
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the solvent on the Lewis acidity of antimony pentahalides and group 13 Lewis acids toward acetonitrile and pyridine

Abstract: Energetic effects of solvation of SbF5, SbCl5, and 21 group 13 Lewis acids (LA) and their molecular complexes with acetonitrile and pyridine are evaluated using SMD approach. Compared to the gas phase, solvation increases the stability of boron‐ and aluminum‐containing complexes but decreases the stability of gallium and indium‐containing homologs due to larger solation energies of free LA. New Lewis acidity scales, based on the Gibbs energy of dissociation of the molecular complexes LA·pyridine and LA·acetoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…The effect of the solvent was estimated using single point energy computations in toluene using SMD 30 method at B3LYP‐D3/def2‐TZVP optimized geometries. It was demonstrated 31 that the geometry optimization in solvent has a little impact on the dissociation energies of the DA complexes of group 13 Lewis acids.…”
Section: Methodsmentioning
confidence: 99%
“…The effect of the solvent was estimated using single point energy computations in toluene using SMD 30 method at B3LYP‐D3/def2‐TZVP optimized geometries. It was demonstrated 31 that the geometry optimization in solvent has a little impact on the dissociation energies of the DA complexes of group 13 Lewis acids.…”
Section: Methodsmentioning
confidence: 99%
“…A recent computational study focused on Gibbs energies of adduct formation between antimony pentahalides and group 13 Lewis acids (among them SbCl 5 and BF 3 ), and the Lewis bases acetonitrile and pyridine, examined the solvent effect on the basis of a continuous dielectric model. The authors concluded that electrostatic, dispersion and electron-repulsive solutesolvent interactions were essential for the prediction of solvation effects [62], while the solvents selected for the study did not include possible hydrogen bond-donor solvents. It is worth mentioning that G4/G4* calculations are not currently possible for antimony pentahalide adducts, in particular for estimating DN via reaction (1).…”
Section: Discussionmentioning
confidence: 99%
“…Scales of MeCN affinities and Py affinities in the gas phase and in nonaqueous solutions, computed at M06-2X/6-311 + + G(2d,p) level of theory (solvation energies were computed using implicit solvation method SMD) were proposed (Figure 10). [108] In 2003, Barron et al used 9-fluorenone (Scheme 8,a) as a reference LB to elucidate the Lewis acidity of group 13 element trihalides MX 3 (M = B, Al, Ga; X = Cl, Br, I). [110] Resulting DA complexes are orange to red solids which were structurally (SCXRD analysis) and spectrally (IR, 13 C NMR, UV-VIS spectroscopy) characterized.…”
Section: Lewis Acidity Scalesmentioning
confidence: 99%
“…Scales of MeCN affinities and Py affinities in the gas phase and in nonaqueous solutions, computed at M06‐2X/6–311++G(2d,p) level of theory (solvation energies were computed using implicit solvation method SMD) were proposed (Figure 10). [108] …”
Section: Lewis Acidity Scalesmentioning
confidence: 99%